Development of Acid-Base Titration Practicum Guide Using Natural Indicators of Butterfly Pea Flowers - Hanifa, Suci Rahma; Ardiansyah, Ardiansyah; Afrianis, Neti; Okmarisa, Heppy (Universitas Pendidikan Mandalika, 2024)
Sustainable Development Goals (SDGs) need to be implemented to create environmentally friendly chemistry learning. This can be done in an acid-base titration experiment using natural indicators of butterfly pea flowers. This research aims to produce a practicum guide for acid-base titrations using natural indicators of butterfly pea flowers that are valid and practicum. The research design uses the ADDIE research design, namely Analysis, Design, Development, Implementation, and Evaluation. The research results showed that butterfly pea flowers can be used as a natural indicator for acid-base titrations with color changes from pink (acidic condition) to blue (basic condition). The resulting learning media is a practicum guide which has a validity of 92% (very valid) and a practicality level of 88.75% (very practical). This data was analyzed using qualitative and quantitative analysis. The practicum guide developed is valid and practical to use as a practicum learning media in schools.